88. Review of nursing home antibiotic stewardship citation deficiencies to identify opportunities to improve antibiotic stewardship implementation, 2018-2019. (4th December 2021) - Gouin, Katryna A; Cool, Andrea J; Stone, Nimalie D; Hicks, Lauri; Jacobs Slifka, Kara M; Almendinger, Katherine; Harmon, Holly; Gifford, David; Truscott, Pamela; Kabbani, Sarah
Abstract: Background: Centers for Medicare & Medicaid Services (CMS) set standards for nursing homes (NH) and conduct inspections to assess adherence to regulatory requirements, including antibiotic stewardship implementation. NHs not meeting requirements are issued a citation. We reviewed text summaries for citations related to antibiotic stewardship to assess implementation in NHs. Methods: We obtained publicly available antibiotic stewardship deficiency citations issued to NHs from 9/2018—7/2019 and NH characteristics data from CMS Nursing Home Compare. We used the χ2 test to compare characteristics of NHs with and without citations. We did a qualitative review of a randomly selected subset (318/635) of antibiotic stewardship citations and classified citations into one or more of four categories based on Centers for Disease Control and Prevention's Core Elements of Antibiotic Stewardship: 1) Leadership & Accountability, 2) Action, 3) Tracking & Reporting, 4) Education (Fig 1). We developed subcategories based on our iterative review process to further describe the citations. Each citation was reviewed by two reviewers and yielded 95% agreement in categorization. Discordant citations were reviewed by a third reviewer, and core element categories with agreement by ≥2/3 reviewers were assigned, resulting in 99% agreement. Antibiotic Stewardship Citation Deficiency Category Common Themes and Examples from Citation Text from Qualitative Review of Antibiotic Stewardship Citation Deficiencies. Results: There were 635 NH stewardship citation deficiencies across 44 states from 9/2018—7/2019. NHs with a citation were more likely to have < 100 beds (60% vs. 50%) and for-profit ownership (75% vs. 70%) (Table 1). Of the 318 reviewed citations, Action was cited in 67% of NHs; 115/213 had missing or incomplete criteria documented for antibiotic initiation. Tracking & Reporting was cited in 40% of NHs; 117/126 had missing or incomplete antibiotic or infection tracking logs. Leadership & Accountability was cited in 23% of NHs; 41/72 NHs had no stewardship policy available. Education was cited in 13% of NHs (Fig 2). Table 1. Characteristics of US Nursing Homes With and Without an Antibiotic Stewardship Citation Deficiency from 9/2018-7/2019. Figure 2. Types of Antibiotic Stewardship Citation Deficiencies in US Nursing Homes, 2018-2019, N=318. Conclusion: The most common opportunities for improvement fell under appropriate assessment and documentation of criteria for antibiotic initiation at the resident and facility-level. Training NH staff to use available resources for antibiotic stewardship activities may improve implementation. Further evaluation to identify barriers to implementation is needed. Disclosures: David Gifford, MD, MPH, American Healthcare Association (Employee)